Cosa sono questi «appunti alla buona dall'aria innocente»? La costruzione delle note etnografiche - Cigliuti, Katia (Premio Ricerca «Città di Firenze», 2014)
The construction process of ethnographic notes suffers from a lack of attention, in particular in relation to the conceptualisation of notes as an object in itself. The risk is the one of leaving one of the key aspects of ethnographic research in the shade and to think of the writing notes process as a non-problematic process of "mere description" of the researcher's presence on the field. The relevance of ethnographic notes is dictated by their being the empirical basis of the observational tool. Studying the notes is important not only because they reveal the reality of the field, but much more because they allow us to confront the construction complexity of the empirical basis of ethnographic research and, ultimately, because they constitue its base of plausibility.